Development and validation of a questionnaire to evaluate the productive engagement of Chinese older adults in the community - Yingjie Shen; Mingli Zhao; Wenya Zhao; Shuangshuang Dai; Xue Wang; Yijia Zhuo (BMC, 2024)
Abstract Background The evaluation of productive engagement of old adults has become a challenging task because cultural, ethical, religious, and other personal values may influence perceptions of the meaning and consequences of productive engagement. Assessing the productive engagement of the older adults is crucial to promote active and productive aging. The objective of this study was to develop and validate a questionnaire concerning the productive engagement of Chinese older adults in the community. Methods A draft scale was created via a literature review and interviews with 17 older adults in the community, following the cross-cultural framework for productive engagement in later life. Content validity was assessed by seven experts. Subsequently, a preliminary questionnaire containing 33 items was developed and its psychometric properties were evaluated. Results The final version of the questionnaire was composed of 27 items distributed across five dimensions. The overall standardized Cronbach's α for the productive engagement questionnaire was 0.904, with individual dimension values ranging from 0.759 to 0.869. Nearly all dimensions displayed satisfactory factor loadings. The correlation coefficient between each item's score and its respective dimension ranged from 0.473 to 0.723. Conclusions The developed questionnaire exhibited good validity and reliability, showing promise for effectively evaluating the productive engagement level of Chinese older adults within the community. Trial registration Not applicable.